Mitigasi Bencana Abrasi Pantai Melalui Penanaman Mangrove di Desa Seriwe, Jerowaru Lombok Timur - Elya Kartika Rinjani; Nurhidayah; Septi Panbriani; Ummi Auliya' Amalina; I Putu Artayasa (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Mangrove forest ecosystem is an important habitat for marine biota and as a coast guard from abrasion. One area that has mangrove forests and is quite vulnerable to abrasion is Seriwe Village, Jerowaru District, East Lombok, NTB. This service activity aims to increase public awareness about the importance of mangrove planting as a disaster mitigation effort in preventing abrasion, especially in Seriwe Village. The activity was carried out by providing counseling to the Seriwe community about the importance of mangrove plants for the life of marine biota, preventing abrasion, and assisting the community in planting mangroves on the coast around the village. This activity involved the University of Mataram Integrated Community Service Program students and villagers. The results of the service showed that this activity ran smoothly and was followed by quite high enthusiasm by all participants. It is hoped that with this activity, the Seriwe Village community can understand and take advantage of mangroves to prevent Seriwe Village from abrasion